"Another high-caste woman beyond his reach": Cast(e)ing the sexual politics of Manu Joseph's Serious Men. (June 2022) - Yadav, Kanak
Indian English Fiction has mostly portrayed Dalit characters from a humanist perspective. Manu Joseph's debut novel Serious Men (2010) departs from such a convention by deploying sexist language to render subversive authority to the Dalit protagonist, Ayyan Mani. While Serious Men (2010) revises the passive depiction of Dalits in Indian English Fiction through its experimental usage of language, its subversion is undermined by its representation of women and lower-caste politics. This article is interested in exploring the intersections between language politics and the politics of caste in the novel, since it seems subversive in expressing the rant of an angry Dalit man, yet it also nevertheless reflects the overt sexualization of urban, upper-caste women. By interrogating the novel's politics of Dalit representation and its critical reception, the article argues how despite satirizing casteist attitudes through the eyes of the Dalit protagonist, the novel inevitably undermines its critique of caste structures through its prejudiced portrayal of women and caste politics.